Detection of residues of β-lactamic antibiotics and tetracyclines in raw milk marketed in Callao - Guerrero A, Dániza M. (2009)
We are analyzed forty samples of raw milk commercialized at the Callao Market between January and March 2009 using presumptive method for β-lactamics and tetracycline antibiotic residues from IDEX laboratories, to comply with the limits of sensitivity of residues of the FDA. We found 40% of samples tested positive for β-lactamic residues in raw milk. There were no positive outcame to analyze tetracyclines. The results suggest that we should establish policies for legislation, regulation and training and that the NTP 202.001.2003 should be reviewed. The results suggested that should be established policies for legislation, regulation and training, and the NTP 202. 00102003 should be reviewed.